From Paper to Structured Carbon Electrodes by Inkjet Printing1. Issue 8 (17th January 2013) - Glatzel, Stefan; Schnepp, Zoë; Giordano, Cristina
<x xml:space="preserve">Abstract</x> Electrodes from the ink‐jet printer: Cellulose sheets can be transformed into mesostructured graphene nanostructures by a simple and general method. Since the iron catalyst can be printed on paper with an ink‐jet printer, the products can be prepared with 2D patterns. Subsequent Cu deposition results in further functionalization of the microstructured electrodes (see picture).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>